A Preliminary Study of Bryophytes in Enggano Island, Bengkulu, Indonesia - Ainun Nadhifah; Muhammad Imam Surya (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Enggano Island is one of the outer islands that belongs to the Province of Bengkulu. Furthermore, there is very limited information about the diversity of bryophyte from Sumatera, especially in lowland forest, Enggano Island. The aim of this research was to provide the initial information related to the diversity of bryophytes in Enggano. The research was conducted in six forests i.e. primary, secondary and degraded forests. The results showed that 32 number of collection from 14 families, 21 genera, and 32 species were identified. Leceuneaceae was common family for liverworts while the mosses family was dominated by Hypnaceae. None of the hornworts were found in this study. Some species identified (Taxyphyllum sp., Vesicularia sp., Riccardia sp., and Thuidium sp.) have the potential benefit and biological activity. Two genera were new records to Sumatra, Gongylanthus, and Symphyogyna. Moreover, Gongylanthus sp. and Symphyogyna sp. have important records related to the habitat.How to CiteNadhifah, A., Surya, M. I. (2016). A Preliminary Study of Bryophytes in Enggano Island, Bengkulu, Indonesia. Biosaintifika: Journal of Biology Biology Education, 8(2), 201-205.